A Comparative Study of Students’ Use of Peer Learning According to Selected Demographics in The Graduate School of Business, Assumption University of Thailand - Sobhanian, Sina; Ye, Yan (Scholar: Human Sciences, 2016)
Peer learning has been shown to be one of the most effective strategies for improving students’ learning, boosting motivation, and strengthening friendship. This study set out to investigate the use of peer learning and to explore the extent to which the students use this strategy in their academic lives. It also aimed to report the differences in the use of peer learning among the students according to the selected demographics. The research involved students from the Graduate School of Business, Assumption University of Thailand. A convenience sampling was used and the data were collected through the researcher-created questionnaire. Findings demonstrated that the students often used peer learning and the learning environment was desirable to encourage this type of learning. At the same time, there were significant differences in the use of peer learning according to the students’ gender, nationality, and employment status. Yet, for the variable of age, no significant difference was found.